Association of Tumor Necrosis Factor Alpha Gene Polymorphisms with Inflammatory Bowel Disease in Iran. - Nosratollah Naderi; Alma Farnood; Tahereh Dadaei; Manijeh Habibi; Hedie Balaii; Farzad Firouzi; Aydin Mahban; Masoumeh Soltani; Mohammadreza Zali (Tehran University of Medical Sciences, 2014)
Inflammatory bowel disease (IBD) is a chronic disease of unknown etiology, in which genetic factors, seem to play an important role in the disease predisposition and course. Assessment of tumor necrosis factor (TNF-α) gene polymorphisms in many populations showed a possible association with IBD. Considering the genetic variety in different ethnic groups, the aim of the present study was to investigate the association of five important single nucleo-tide polymorphisms (SNPs) in the promoter region of (TNF-α) gene with IBD in Iran.In this case-control study, 156 Ulcerative colitis (UC) patients, 50 Crohn's disease (CD) patients and 200 sex and age matched healthy controls of Iranian origin were enrolled. The study was performed during a two year period (2008-2010) at Taleghani Hospital, Shahid Beheshti University of Medical Sciences, Tehran, Iran. DNA samples were evaluated for (TNF-α) gene polymorphisms (including -1031, -863, -857, -308 and -238) by PCR and RFLP methods.The frequency of the mutant allele of -1031 polymorphism was significantly higher in Iranian patients with Crohn's disease compared to healthy controls (P=0.01, OR=1.92; 95% CI: 1.14-3.23). None of the other evaluated polymorphisms demonstrated a significant higher frequency of mutant alleles in Iranian IBD patients compared to controls.Among the five assessed (SNPs), only -1031 polymorphism of (TNF-α) gene may play a role in disease susceptibility for Crohn's disease in Iran. This pattern of distribution of (TNF-α) gene polymorphisms could be specific in this population.